Accuracy of the Multinational Association of Supportive Care in Cancer (MASCC) and Clinical Index of Stable Febrile Neutropenia (CISNE) scores for predicting serious complications in adult patients with febrile neutropenia: A systematic review and meta-analysis. (May 2020) - Zheng, Bo; Toarta, Cristian; Cheng, Wei; Taljaard, Monica; Reaume, Neil; Perry, Jeffrey J.
Abstract: We compared the Multinational Association of Supportive Care in Cancer (MASCC) and Clinical Index of Stable Febrile Neutropenia (CISNE) scores for identifying serious complications in febrile neutropenia patients. We searched MEDLINE, PubMed, EMBASE, and Cochrane Database of Systematic Reviews from inception to March 19, 2019. Two reviewers independently screened citations, extracted data, and assessed quality. We included 26 studies, totalling 6617 patients. Pooled sensitivity and specificity for MASCC < 21 was 55.6 % (95 % CI: 46.2 %–64.5%) and 86.0 % (95 % CI: 81.3 %–89.7 %), respectively. Pooled sensitivity and specificity for CISNE ≥ 3 was 78.9 % (95 % CI: 65.3 %–88.1 %) and 64.9 % (95 % CI: 49.6 %–77.7 %), respectively. Pooled sensitivity and specificity for CISNE ≥ 1 was 96.7 % (95 % CI: 93.6 %–98.3 %) and 22.2 % (95 % CI: 15.6 %–30.4 %), respectively. The CISNE score had higher sensitivity and may be more useful than the MASCC score in the acute setting.